Mesenteric hypoperfusion and inflammation induced by brain death are not affected by inhibition of the autonomic storm in rats (Clinics, 2015)
OBJECTIVES: Brain death is typically followed by autonomic changes that lead to hemodynamic instability, which is likely associated with microcirculatory dysfunction and inflammation. We evaluated the role of the microcirculation in the hemodynamic and inflammatory events that occur after brain death and the effects of autonomic storm inhibition via thoracic epidural blockade on mesenteric microcirculatory changes and inflammatory responses. METHODS: Male Wistar rats were anesthetized and mechanically ventilated. Brain death was induced via intracranial balloon inflation. Bupivacaine (brain death-thoracic epidural blockade group) or saline (brain death group) infusion via an epidural catheter was initiated immediately before brain death induction. Sham-operated animals were used as controls (SH group). The mesenteric microcirculation was analyzed via intravital microscopy, and the expression of adhesion molecules was evaluated via immunohistochemistry 180 min after brain death induction. RESULTS: A significant difference in mean arterial pressure behavior was observed between the brain death-thoracic epidural blockade group and the other groups, indicating that the former group experienced autonomic storm inhibition. However, the proportion of perfused small vessels in the brain death-thoracic epidural blockade group was similar to or lower than that in the brain death and SH groups, respectively. The expression of intercellular adhesion molecule 1 was similar between the brain death-thoracic epidural blockade and brain death groups but was significantly lower in the SH group than in the other two groups. The number of migrating leukocytes in the perivascular tissue followed the same trend for all groups. CONCLUSIONS: Although thoracic epidural blockade effectively inhibited the autonomic storm, it did not affect mesenteric hypoperfusion or inflammation induced by brain death.